Symposium on art aesthetics and international Justice. Introduction to the symposium on art aesthetics and international courts - Aksenova, Marina (Cambridge University Press, 2020)
This essay provides a general framework for thinking about art and international justice,and more specifically the work of international courts. As international justice searches for new methodologies and instruments of inquiry,aesthetic experience proves to be a lens through which it is possible to deepen our understanding of international justice as a specific social practice in its dynamic form. Art is both a representation of reality and an affective state in which both participants in judicial proceedings and outside observers can interact and experience justice directly. This essay and the symposium as a whole demonstrate that art is implicit in the rhetoric of international courts,their architectural design,and their commemorative practices expressed by symbolic reparations and outreach activities. © Marina Aksenova 2020. This is an Open Access article,distributed under the terms of the Creative Commons Attribution licence
Keywords: ODS 4 - Educación de calidad